Dynamics Study of the OH + O3 Atmospheric Reaction with Both Reactants Vibrationally Excited - Zhang, Lei (2006)
The dynamics of the title five-atom atmospheric reaction is studied by the quasiclassical trajectory method for vibrational states of OH over the range 2 ≤ v ≤ 9 and initial vibrational energies of O3 between 9 and 21 kcal mol-1 using a previously reported double many-body expansion potential energy surface for HO4(2A). The results show that the reaction is controlled by both capture- and barrier-type mechanisms, with the rate constants depending strongly on the reactants' internal energy content. Also suggested from the magnitude of the calculated rate coefficients is that the title processes may not be ignorable when studying the stratospheric ozone budget.